Injury surveillance in elite Paralympic athletes with limb deficiency: a retrospective analysis of upper quadrant injuries - Heneghan, N. R.; Heathcote, L.; Martin, P.; Spencer, S.; Rushton, A. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: Compared to injury surveillance in Olympic athletes relatively little literature exists for Paralympic athletes. Injury surveillance data underpin design and evaluation of injury prevention strategies in elite sport. The aim of this study is investigate upper quadrant injuries in elite athletes with limb deficiency. Methods A retrospective analysis of upper quadrant injuries in elite athletes with limb deficiency with available data (2008-2016) was conducted using medical notes extracted from English Institute of Sport (EIS) records. Eligibility criteria included funded athletes, eligible for EIS physiotherapy support with an upper and/or lower limb disability arising from full or partial limb deficiency. Results A total 162 injuries from 34 athletes were included. Participant characteristics: 20 males (59%), from 9 sports, with mean age 27?years (range 16-50 years) and 15 with congenital limb loss (44%). Athletes age 20-29 years experienced most injuries, four per athlete. The glenohumeral joint was the reported injury site (23%, n=38). Index (first) injuries accounted for 77% (n=128) injuries, 17% (n=28) a recurrence and 6% (n=10) an exacerbation. More than half of injuries occurred in training (58%, n=94), this being slightly higher in those with traumatic limb loss. Athletes with quadruple levels of limb deficiency had double the number of recurrent injuries as those with single or double limb deficiency. Conclusion Elite athletes with limb deficiency experience upper quadrant injuries, with glenohumeral joint the most frequently reported. The quality and consistency of data reported limits definitive conclusions, although findings highlight the importance of precision and accuracy in recording injury surveillance to enable implementation of effective injury prevention strategies.